Generalized Tetanus in A Patient with Infected Sutured Wound: A Case Report - Novi Tejaya; Marina Musyawwirina Desiprimayanti Ruslan Ramli (AKSONA, 2023)
Highlight: Tetanus in patients with infected sutured wound. Complications of death in generalized tetanus. The importance of education about tetanus.   ABSTRACT Introduction: Tetanus is a disease caused by Clostridium tetani, which produces an exotoxin. Tetanus can rapidly progress into life-threatening muscle spasms accompanied by respiratory insufficiency with or without autonomic dysfunction. Case: A 43-year-old male patient was referred from the public health center to Tora Belo Hospital with mouth stiffness and difficulty swallowing food. He also had stiffness and pain in the neck, abdomen, and lower back. Seven days prior, the patient received lacerations on his right forearm caused by a machete. The patient’s wound had been stitched up without an anti-tetanus injection at the public health center. The symptoms worsened on the second day of admission, and the patient died from respiratory failure. Conclusion: It is very important to enhance public awareness that tetanus is a preventable disease, with proper vaccination and sanitization potentially lowering mortality and morbidity.